(untitled) (Swiss Medical Weekly, 2016)
At the end of life, several treatments are administered routinely that lack medical indication and may cause significant harm to patients. Examples include artificial hydration and oxygen therapy in the dying phase, as well as enteral nutrition in advanced dementia. Medical indication is defined as the appropriateness of a therapeutic or diagnostic measure in the patient’s concrete clinical situation, in light of the best available evidence. The decision about the absence or presence of a medical indication is a core competence of physicians. They have no obligation to perform or even mention measures that are not indicated. The decision about medical indication is a clinical compound decision, composed of both a factual, evidence-based judgement and a value judgement, which should always be patient-centred. Acknowledging the crucial role of medical indication in clinical decision making in medicine generally and at the end of life specifically opens up ways of enhancing patient-physician communication by clarifying roles, responsibilities and competencies. This may facilitate preventing overtreatment, improving patient wellbeing, and realising the patients’ goals of care.